Analisis Wacana Ekspresi Kecemasan dalam Media Sosial: Kajian Pragmatik Tuturan Remaja dengan Fenomena Fomo - Dea F, Ananda; Kheyla Ayu N.D; Aulia, Nadila Rahma; Riski, Yurika Nur; anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
The phenomenon of Fear of Missing Out (FOMO), or the fear of being left behind in the flow of information and social interaction, is one of the factors that influence the psychological condition of adolescents in their use of social media. This study aims to analyse the forms of discourse expressing adolescent anxiety that appear on social media and to examine this phenomenon from a pragmatic perspective. This study uses a qualitative approach with pragmatic discourse analysis methods. Data in the form of adolescent speech quotations were collected from Instagram, X, and TikTok platforms by searching for hashtags relevant to the FOMO phenomenon. The results show that adolescents' expressions of anxiety due to FOMO are not always conveyed explicitly but are present in the form of implied meanings through certain word choices and language styles. Words such as ‘left behind’ or ‘out of date’ indicate a concern about missing important moments, while pragmatic strategies such as humour, irony, and repetition are used to mask feelings of anxiety. Teenagers' speech also reflects social pressure from their peer environment, which influences the way they communicate in the digital world. These findings confirm that FOMO plays an important role in shaping digital communication patterns and impacts the mental health of teenagers. Through pragmatic analysis, the results of this study can form the basis for the development of healthier digital literacy and strategies to prevent the negative impacts of social media.